(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective : To determine the rate of local inflammation in patients with peripheral venous catheters and to analyze some related factors. Research method : A cross-sectional descriptive study with analysis was conducted on 240 patients and 545 peripheral venous catheters observed. Results : The rate of phlebitis in patients with peripheral venous catheters assessed by the Visual Infusion Phlebitis scale was 27.5% for patients and 25.9% for peripheral venous catheters. The most common levels of inflammation were grade 1 (37.2%) and grade 2 (24.2%); a small number had grade 3 inflammation (1.7%); no grade 4 or grade 5 inflammation was detected. Factors related to the increased rate of phlebitis include: age ≥ 60, low body mass index (BMI < 18.5); treatment duration ≥ 5 days; medication use > 2 times/day, use of more than 2 types of antibiotics and use of antibiotics from the Cephalosporin, Quinolones groups; catheter insertions ≥ 3 times. The risk of developing phlebitis when the peripheral venous catheter is placed at the elbow/leg is 3 times higher than the back of the hand. Conclusion : The rate of local inflammation in patients with peripheral venous catheters was 25.9%. Early monitoring and detection of localized phlebitis are essential to improve the quality of patient care.